2018
DOI: 10.1103/physrevc.97.044915
|View full text |Cite
|
Sign up to set email alerts
|

Vortex rings in fragmentation regions in heavy-ion collisions at sNN=39 GeV

Abstract: Vorticity generated in heavy-ion collisions at energy of √ sNN = 39 GeV is studied. Simulations are performed within a model of the three-fluid dynamics. A peculiar structure consisting of two vortex rings is found: one ring in the target fragmentation region and another one in the projectile fragmentation region. These rings are also formed in central collisions. The matter rotation is opposite in this two rings. These vortex rings are already formed at the early stage of the collision together with primordia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Numerical calculations with transport-hybrid codes (96,99,102) also indicate a forward migration of vorticity, especially as the collision energy increases (99). Finally, hydrodynamic models predict much higher vorticity in the beam fragmentation region at both NICA (97, 146) and RHIC (92,147) energies. Exploring vorticity away from midrapidity in fixed-target experiments (discussed above) is relatively straightforward.…”
Section: 43mentioning
confidence: 82%
See 1 more Smart Citation
“…Numerical calculations with transport-hybrid codes (96,99,102) also indicate a forward migration of vorticity, especially as the collision energy increases (99). Finally, hydrodynamic models predict much higher vorticity in the beam fragmentation region at both NICA (97, 146) and RHIC (92,147) energies. Exploring vorticity away from midrapidity in fixed-target experiments (discussed above) is relatively straightforward.…”
Section: 43mentioning
confidence: 82%
“…For particles emitted at forward rapidity, symmetry permits an average polarization projection alongn =b. In fact, so-called vortex rings or cyclones are predicted (100,147) at forward rapidity at RHIC (100) and NICA (97, 147) energies (4 GeV √ s NN 11 GeV) as well as at midrapidity in nonsymmetric systems (149). In this case,n p ×ẑ.…”
Section: Other Polarization Projectionsmentioning
confidence: 99%
“…See Refs. [22,23,[31][32][33][34][35] for other calculations of the quadrupole structure of ω y . Figure 4 shows the distribution of ω ⊥ = (ω x , ω y ) as functions of x and y at two values of space-time rapidity η s = −1 and 1.…”
Section: Fluid Velocity and Vorticity Fields And Polarization DImentioning
confidence: 99%
“…However, the local vorticity field has much richer information than the global one. In the numerical simulations [22,23,[31][32][33][34][35], it is observed that ω y shows a quadrupole pattern in the reaction plane (xz plane): ω y is negative and positive in the regions xz > 0 and xz < 0, respectively. This novel structure is mainly due to the fact that the transverse velocity |v x | decreases with rapidity or ∂|v x |/∂|z| < 0 [33].…”
Section: Introductionmentioning
confidence: 99%
“…In HIC this corresponds to the hadronic beams [15] (being most close to the discussed liquid helium example) and jets [16]. One may also consider the rings appearance and evolution in the case of HIC, where 3-fluid hydro [19] or kinetic model [20] can be applied.…”
Section: Vortex Rings Local Polarization and Handednessmentioning
confidence: 99%